2001
DOI: 10.1021/ol0169168
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Highly Regio- and Chemoselective Cocyclotrimerization of Propiolates with Allenes:  A Novel Route to Polysubstituted Benzene Derivatives

Abstract: The Ni(dppe)Br(2)/Zn system effectively catalyzes the cocyclotrimerization of propiolates with allenes. The reaction is highly regio- and chemoselective to afford polysubstituted benzene derivatives in good to excellent yields. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…It is noteworthy that the reaction proceeded satisfactorily without the need for the electron‐withdrawing CO 2 R group, which had proven crucial in other [2+2+2] cycloaddition reactions involving allenes 7a. c, 8, 10 The yields for the allene–yne–allene substrates were lower than those for the allene–ene–allene substrates due to the increased decomposition observed during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the reaction proceeded satisfactorily without the need for the electron‐withdrawing CO 2 R group, which had proven crucial in other [2+2+2] cycloaddition reactions involving allenes 7a. c, 8, 10 The yields for the allene–yne–allene substrates were lower than those for the allene–ene–allene substrates due to the increased decomposition observed during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, similar transformations using allenes in place of alkenes have been reported in a limited number of examples . As examples of the cross‐cyclotrimerization of alkynes with allenes, the nickel‐catalyzed reactions of one molecule of a monosubstituted allene with two molecules of an electron‐deficient internal alkyne followed by aromatization through olefin isomerization, which affords the corresponding pentasubstituted benzenes, has been reported (Scheme a) . However, the usable alkynes are limited to electron‐deficient alkynoates, and electron‐rich alkynes cannot be employed .…”
Section: Methodsmentioning
confidence: 99%
“…As examples of the cross‐cyclotrimerization of alkynes with allenes, the nickel‐catalyzed reactions of one molecule of a monosubstituted allene with two molecules of an electron‐deficient internal alkyne followed by aromatization through olefin isomerization, which affords the corresponding pentasubstituted benzenes, has been reported (Scheme a) . However, the usable alkynes are limited to electron‐deficient alkynoates, and electron‐rich alkynes cannot be employed . Furthermore, a selective and general method for the cross‐cyclotrimerization of two molecules of an allene and one molecule of an alkyne has not been reported to date .…”
Section: Methodsmentioning
confidence: 99%
“…Cheng et al [31][32][33] made a substantial contribution to the topic by systematically studying the intermolecular cycloaddition of allenes with alkynes and diynes (Scheme 15). In these studies, the less substituted double bonds of the allenes were found to participate in the cycloaddition.…”
Section: Intermolecular and Partially Intermolecular Cycloadditions Omentioning
confidence: 99%
“…Therefore, the allenes acted here as synthetic equivalents of monosubstituted alkynes. The first study by Cheng et al 31 was based on a completely intermolecular reaction between two molecules of alkyne and one molecule of allene under nickel catalysis, to afford polysubstituted benzene derivatives in a highly regioand chemoselective fashion (Scheme 15a). The best catalytic system found was [Ni(dppe)Br 2 ] with an excess of metallic Zn as the reductant of Ni(II) to Ni(0), which was the actual catalytic species.…”
Section: Intermolecular and Partially Intermolecular Cycloadditions Omentioning
confidence: 99%